Facile synthesis of g-C3N4/BiOClxI1-x hybrids with efficient charge separation for visible-light photocatalysis. Issue 8 (1st June 2020) - Sun, Xinyue; Du, Yi; Li, Zhongfu; Chen, Shunwei; Feng, Yibing; Jiang, Nan; Liu, Yang; Wang, Jiajia; Li, Haoyu
Abstract: At present, most common catalysts are faced with the problem of high cost and only visible light response. Graphitic carbon nitride (g-C3 N4 ) consists of elements C and N that are sufficiently abundant in the world and has visible light responses, but the electron-hole recombination rate of this photocatalyst is high. In this work, we directly prepare a series of g-C3 N4 -bismuth oxyhalides composites via facile in-situ deposition. Bismuth oxides with different chloro-iodine ratios (BiOClx I1-x ) are prepared, followed by g-C3 N4 deposition, setting up interfaces and improving photogenic charge carriers transfer. By testing the compositions, Cl:I = 8:2 in BiOClx I1-x and 10% of g-C3 N4 doping amount enable the best photocatalytic performance of the samples. Under visible light irradiation, the degradation rate of rhodamine B (RhB) reaches 99% within 40 min. Through a variety of tests, the photogenerated hole (h + ) and superoxide radical (O2 − ) are found to play key roles in the degradation process. Cl element doping and heterojunction building improve the photocatalysis capacity of g-C3 N4 and broaden the visible-light response of pure BiOI.